Melt inclusion bubbles provide new insights into crystallisation depths and CO2 systematics at Soufrière Hills Volcano, Montserrat - Howe, TiVonne A.; Christopher, Thomas E.; Moune, Séverine; Tuffen, Hugh; Schiavi, Federica (Frontiers in Earth Science, 2025)
Improved understanding of the magmatic system of Soufrière Hills Volcano, Montserrat (SHV) is needed to inform future hazard management strategy, and remaining uncertainties include the depth of magma storage and the source of ongoing gas emissions. Eruptive activity between 1995 and 2010 has been proposed to be sourced from either a dual chamber or transcrustal mush-based magmatic system, with volatile solubility models using H2O and CO2 from melt inclusion (MI) glass estimating depths of 5–6 km. To date, published SHV MI volatile data have neglected the vapour bubbles now known to sequester the bulk of MI magmatic carbon. Total CO2 concentrations in SHV magma are therefore underestimated, together with volatile-derived entrapment pressures and inferred magma storage depths. Here, we present a new dataset of volatile (H2O and total CO2) and major element concentrations in plagioclase- and orthopyroxene-hosted SHV MI, that span almost all of the eruptive activity (Phases 1, 2, 4, and 5), and include the first measurement of bubble-hosted CO2 for SHV and indeed the Lesser Antilles Arc. Analyses were conducted using Raman spectroscopy, ion microprobe, and electron probe analysis. Dacitic–rhyolitic MI occur within andesitic whole rock compositions. Volatiles in MI glass are similar to published studies (H2O 2.47–7.26 wt%; CO2 13–1243 ppm). However, bubble-hosted CO2 contributes 9–3,145 ppm, to total inclusion CO2 with 5%–99% (median 90%) of CO2 sequestered within bubbles, and total CO2 concentrations (131–3,230 ppm) are significantly higher than previously published values. Inferred entrapment depths from our dataset range from 5.7 to 17 km – far greater than previous estimates – and support a vertically elongated magmatic system where crystallisation spanned both upper- and mid-crustal depths. Our CO2 measurements enable new estimation of CO2 sources and fluxes. As a total of 4.5 Mt of CO2 was held in SHV magma during the aforementioned phases, the maximum amount of CO2 that can be emitted from a batch of SHV magma is ∼1500–1750 tonnes/day. Measured CO2 fluxes are significantly higher, indicating additional input of CO2 into the system from greater depths. Our study shows that including bubble-hosted CO2 redefines understanding of the SHV plumbing system.